Penerapan Prinsip Good Corporate Governance (Gcg) Dalam Pengelolaan Zakat (Study Di Lembaga Amil Zakat Dompet Dhuafa Yogyakarta) - Endriyana, Endriyana, Mutimatun Ni'ami, S.H., M.Hum, ARISTYA WINDIANA P., S.H., LLM (2016)
The growth of zakat market continues to increase from year to year, needed a system which can be applied in amil zakat institutions for collection, management, distribution and utilization by make into Good Corporate Governance principle as standardization of zakat management. Using empirical juridical methods is the way the procedures are used to solve research problems by examining secondary data then followed by conducting research on primary data in the field. To prove the application of the principles of Good Corporate Governance which include transparency, ccountability, responsibility, and fairness in the amil zakat institutions Dompet Dhuafa Yogyakarta and understand the rules associated with zakat. These aspects are customizable. Barriers and benefits in application of the principles of good corporate governance as the basis reference of other amil zakat institutions in applying the principles of Good Corporate Governance.